2022
DOI: 10.1097/scs.0000000000008486
|View full text |Cite
|
Sign up to set email alerts
|

Update: Diversity and Practice Patterns of International Craniomaxillofacial Surgeons

Abstract: Background: The authors’ group characterized the cranio-maxillo-facial workforce 10 years ago, revealing high levels of career satisfaction but significant gender disparity. This study provides an updated profile of the international cranio-maxillo-facial workforce. Methods: A 30-question electronic survey was distributed to 387 cranio-maxillo-facial surgeons with membership in the American Society of Craniofacial Surgeons, American Society of Maxillofacial Surgeons, and international Society of Craniofacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Results from this study may further underscore the importance of cultivating a diverse team and surgical workforce to optimally treat patients from a variety of socioeconomic backgrounds. 27 This study has several limitations. The retrospective approach precludes establishment of causal relationships.…”
Section: Discussionmentioning
confidence: 92%
“…Results from this study may further underscore the importance of cultivating a diverse team and surgical workforce to optimally treat patients from a variety of socioeconomic backgrounds. 27 This study has several limitations. The retrospective approach precludes establishment of causal relationships.…”
Section: Discussionmentioning
confidence: 92%
“…[11][12][13] A 2022 study regarding diversity and practice patterns among international craniomaxillofacial surgeons found that female surgeons had earlier retirement plans and experienced more discrimination compared with their male colleagues. 8 Moreover, a potential barrier to having less female representation at the top of the academic ladder is that fewer female trainees can find guidance from a mentor who has achieved the position or career they strive to.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have examined diversity in craniofacial surgery from the overall perspective of the international community, representation in published clinical photographs, speakers at national meetings, and authorship in peer-reviewed reconstructive journals, but the literature has yet to explore a broad analysis of leadership ranging from fellowship program faculty positions, editorial boards of major journals, and prominent national societies at a specific point in time or a single investigation. 6,[8][9][10] The additional granularity provided by our study examines possible regional differences and the time period that formal training was completed, providing future studies an opportunity to examine sex trends from a more temporospatial and quantitative perspective. Having multiple avenues to assess the diversity of craniofacial surgery across these important leadership roles can offer an effective method of reviewing progress toward the goal of equitable representation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated more than 20% of craniomaxillofacial surgeons identify with a sexual orientation other than heterosexual, 4 and similar studies characterizing LGBTQ diversity in other subspecialties may be helpful to identify areas prime for targeted intervention. While overall representation is certainly an important first step, additional data reflecting LGBTQ diversity by academic rank may yield insights to attrition in ascension from trainee to academic leadership, previously described as the “leaky pipeline” for racial and ethnic minorities in plastic surgery 5 …”
mentioning
confidence: 99%
“…A previous abstract revealed about 8% of plastic surgery respondents identified as LGBT, 2 which matches the US general population at approximately 7%, 3 yet polls demonstrate more than 20% of the youngest "Generation Z" identify as LGBTQ, which may in part explain the recent exponential demand for gender-affirming care. 3 A recent study demonstrated more than 20% of craniomaxillofacial surgeons identify with a sexual orientation other than heterosexual, 4 and similar studies characterizing LGBTQ diversity in other subspecialties may be helpful to identify areas prime for targeted intervention. While overall representation is certainly an important first step, additional data reflecting LGBTQ diversity by academic rank may yield insights to attrition in ascension from trainee to academic leadership, previously described as the "leaky pipeline" for racial and ethnic minorities in plastic surgery.…”
mentioning
confidence: 99%